Analysis Of Internal And External Factors On Consumer Purchase Decisions At Teko Healthy Resto - Shery; Nugroho, Ngajudin (Journal Boas : Business, Economics, Accounting And Management, 2023)
This study aims to examine internal and external factors on purchasing decisions at Teko Healthy Resto. The object of this research is Teko Healthy Resto consumers. The basis of the selection of this sample is the interview method. The data applied in this study are primary data, data obtained from questionnaires distributed to 30 respondents. According to the results and conclusions, the understanding shows that: (1)Consumers feel very impressed and they like the atmosphere in Teko healthy Resto suits them. (2)Perception of some consumers, Teko Healthy Resto is a restaurant selling a variety of food at a slightly expensive price, cleanliness of the place is maintained and a good place with sufficient facilities.(3)That most consumers visit Teko Healthy Resto are customers who already know Teko Healthy Resto.(4)Vegetarian food brings positive things to customers. This matter can once provide motivation for those who want to pay attention to the body.(5)Teko Healthy Resto can attract consumers with its design and stunning interiors.(6)Teko Healthy Resto, has a good level of social class. So it fits for today's lifestyle, namely young people.(7)Teko Healthy Resto has a well-known name in the audience. Consumers who have never visited also become curious. (8) The facilities provided by Teko Healthy Resto, Medan are sufficient 2satisfying. However, there are a few things to note again such as gloves and some food courts.